Bibliometric Analysis of Research Trends on Filtration and Quality of Waste Liquid in Hospitals - Sapta Heru Purnama; Eko Suhartono; Isna Syauqiah; Lenie Marlinae; Ardik Lahdimawan (Malahayati Nursing Journal, 2024)
ABSTRACT This study aims to conduct a bibliometric analysis of research trends regarding filtration and liquid waste quality in hospitals from 2018 to 2024. Using the Google Scholar database and bibliometric analysis applications such as VOSviewer, this study identified and analyzed relevant publications with the keywords filtration, effluent, hospital, COD, BOD, and Liquid Waste Quality. The data obtained was processed with occurrence 4 and term 20 parameters to identify the main patterns and trends in the literature. The analysis results show that the number of publications has increased significantly from year to year, with peaks in 2021 and 2022. The distribution of publication types shows the dominance of research articles with 42 out of 50 publications, followed by literature reviews (3) and conference articles (4). Analysis based on country of publication revealed the dominance of Indonesia with 23 publications, followed by India and several other countries with smaller contributions. Cluster analysis based on network visualization identified four main clusters: (1) effluent quality parameters such as BOD and COD; (2) hospital effluent management; (3) effluent treatment and management; and (4) effluent quality characterization and assessment.The results of density visualization showed a high concentration of quality parameters and treatment technologies, while overlay visualization revealed a close relationship between quality parameters and effluent management. The conclusions of this study highlight the major focus on technical parameters of effluent quality and treatment technology, as well as the importance of integration between effluent management and quality evaluation in research. The findings offer valuable insights for further research and development of innovative solutions in effluent management in hospitals. Keywords: Bibliometrics, Filtration, Effluent Quality, Hospital, Network Analysis